Biochemical Integration of Chemically Modified Carbon Nanotubes - Akpor Ugochukwu Blessed (Lembaga Yasin AlSys, 2025)
Carbon nanotubes (CNTs) have attracted growing interest in recent years for their small size, ordered structure, and distinctive surface and atomic configurations that enable applications across biomedicine and materials science. The objective of this study is to synthesize current knowledge on CNTs, how they are defined, classified, arranged, and synthesized; their unique properties; and their applications and risks with emphasis on drug delivery and broader biomedical uses. Methodologically, the paper conducts a literature-based review of CNT properties and uses, including their roles as carriers for therapeutic molecules (e.g., peptides), biosensors, and components in molecular electronics and composite materials, as well as hazards, regulatory considerations, and medical status. Key findings indicate that CNTs are promising, biocompatible, and supportive materials for transporting therapeutics owing to their internal cavity and ease of coating with biocompatible chemicals; they can be readily taken up by cell membranes and have been reported to deliver drugs directly to cancer cells. Beyond biomedicine, CNTs’ structural and surface features support their application as biosensors and in molecular electronics and composite formulations. The study concludes that CNTs offer substantial potential for targeted drug delivery and multimodal biomedical uses while requiring careful consideration of hazards and regulatory frameworks. The contribution and implication are a consolidated overview that highlights largely untapped opportunities for CNTs in biological research and clinical translation alongside the need for systematic evaluation of safety and oversight.